Utilization of treatment by Medicaid enrollees with opioid use disorder and co-occurring substance use disorders. (1st December 2020) - O'Brien, Peggy; Henke, Rachel Mosher; Schaefer, Mary Beth; Lin, Janice; Creedon, Timothy B.
Highlights: About half of those with opioid use disorder had another substance use disorder. Compared with their counterparts with opioid use disorder only, these adults were— Less likely to use opioid use disorder medication treatment More likely to receive intensive services Barriers to outpatient care for these adults must be addressed. Abstract: Background: Multiple substance use is common among adults who misuse opioids. Adverse consequences of drugs are more severe among multisubstance users than among single drug users. This study sought to determine whether adults with opioid use disorder (OUD) and at least one other substance use disorder (SUD) are less likely than adults with OUD only to receive certain services. Methods: We conducted a retrospective longitudinal study using the IBM® MarketScan® Multi-State Medicaid Database. We used logistic regression to measure associations between clinical characteristics and service utilization. The sample included non-Medicare-eligible adults aged 18–64 years with at least one claim in 2016 with a primary diagnosis of OUD who were continuously enrolled in Medicaid in 2016 and 2017. Results: Of the 58, 745 Medicaid enrollees with an initial OUD diagnosis in 2016, 29, 267 had one or more additional SUD diagnoses. In the year following diagnosis, these adults were less likely than adults with OUD only to receive OUD medication treatment (OR = 0.88, p < .0001). This was true for all specifically diagnosed co-occurring SUDS. Adults with OUD and a co-occurring SUD, however, were more likely than those with OUD only to use any type of high-intensity services. Conclusions: Adults with OUD and at least one co-occurring SUD received more intensive services, which may reflect severity and lack of OUD medication treatment before misuse escalation. Programs should account for barriers to connecting these individuals to appropriate OUD treatment.